Analysis Visitor Satisfaction Level of Outdoor Recreation in Bogor Botanical Gardens - Irfan, Muhammad; Dinitri, Seruni (Prasetiya Mulya Publishing, 2021)
Bogor Botanical Gardens is a conservation area that has long been used by the wider community as a tourist attraction and has become one of the most popular tourist destinations because it presents a panoramic view of natural landscape architecture. This research was conducted to find out how Outdoor Recreation in Bogor Botanical Gardens can provide tourist satisfaction and how the influence of Outdoor Recreation on tourist satisfaction. The purpose of this study is to analyze Outdoor Recreation in the level of tourist satisfaction, and how much influence Outdoor Recreation has on tourist satisfaction. The research method used is the Importance Performance Analysis (IPA) Method with the aim to provide an illustration and illustrate the gap between the interests and satisfaction of individual attributes both of which are easy to understand and understand well through these measurements. Quantitative methods, to obtain more comprehensive data, do valid and reliable testing. The results of the merging of the performance of Bogor Botanical Gardens (performance) and the level of tourist expectations (Importance). divided into 4 quadrants as an indicator of overall tourist satisfaction through 100 respondents. The determination of the position of the 11 research attributes is determined based on the average value of both the level of importance and performance. Determination of the X (performance) of 3.62 and Y (Importance) of 3.63, obtained from the total average of all 11 average values for both the performance of the Bogor Botanical Garden (performance) and the level of tourist expectations (Importance).Through this research phase, it is expected that there will be an increase in tourist facilities by the Bogor Botanical Gardens, so that it can provide satisfaction in accordance with the expectations of tourists during the tour and create sustainable tourism in every tourist attraction in the Botanical Gardens